Anti-inflammatory Activity of Clitoria ternatea L. and Hibiscus sabdariffa L. Extract Combination in Reducing VCAM-1 Levels in Atherosclerosis - Harefa, Karnirius; Ritonga, Ahmad Hafizullah; Safitri, Riri; Aritonang, Barita (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Atherosclerosis occurs when plaque accumulates and hardens within the arterial walls, leading to blood vessel blockages and increasing the risk of coronary heart disease (CHD). The extracts of butterfly pea (Clitoria ternatea L.) and roselle (Hibiscus sabdariffa L.) contain flavonoids that possess strong antioxidant and anti-inflammatory properties. This study aims to assess the effects of the combined extract of butterfly pea and roselle (EKTR) on atherosclerosis biomarkers such as Vascular Cell Adhesion Molecules-1 (VCAM-1), Intercellular Adhesion Molecule-1 (ICAM-1), and Interleukin-6 (IL-6). The research employed a True Experimental Laboratory approach using a Post-Test Control Group Design. The subjects were 36 female Wistar rats (Rattus norvegicus L.), randomly divided into six groups through a Completely Randomized Design (CRD). Data were collected on the levels of VCAM-1, ICAM-1, and IL-6 in the serum of obese white rats, measured using an ELISA photometer. Data analysis was conducted using SPSS version 18, with statistical evaluation performed via one-way ANOVA and Tukey's post hoc test. The results showed that increasing doses of EKTR led to significant reductions in atherosclerosis biomarkers such as VCAM-1, ICAM-1, and IL-6 compared to the positive control and other groups. At a dose of 500 mg/kg BW, group F3 recorded IL-6 levels of 30.49 ± 1.60 ng/mL, VCAM-1 level of 29.42 ± 2.58 ng/mL, and ICAM-1 levels of 28.42 ± 1.72 ng/mL. In conclusion, butterfly pea and roselle, rich in flavonoids with potent antioxidant and anti-inflammatory properties, are effective as traditional remedies for reducing atherosclerosis biomarkers and for preventing and treating coronary heart disease (CHD) at an optimal dose of 500 mg/kg BW.